Patent Licensing, Non‐Practising Entities, and Investment in R&D. (4th July 2022) - Bergin, James
Abstract: This paper studies the impact of Non‐Practising Entities (NPE's) on investment in innovation. The issue is considered in an environment with strategic investment behavior and licensing. Patent strength turns out to be central in determining the impact of an NPE on innovation. A patenting scheme which assigns rights only to incremental innovation improvement (relative to the innovations of competitors) raises aggregate investment relative to a 'winner‐takes‐all' scheme. In a 'winner‐takes‐all' scheme the most successful/encompassing innovation obtains all the intellectual property rights, and less successful innovators none, and in this environment the presence of an NPE negatively impacts aggregate investment.